ANALISIS FAKTOR PENDORONG DAN FAKTOR PENGHAMBAT PENGEMBANGAN AGRIBISNIS PERIKANAN TANGKAP DENGAN PENDEKATAN SUBSISTEM DI KABUPATEN PENAJAM PASER UTARA - Novita Putri Setiawati (Jurnal Planologi, 2021)
The marine fishery production of Penajam Paser Utara was 6,045 tons per year of 2018 which was close to the national production number. In addition, fishery is a leading sector after agriculture in PPU which will be developed, the fisheries sector should be able to contribute to a large GDP as well, but this was not in line because seeing the contribution of the fisheries sector to GRDP, constant prices from 2012 to 2016 have decreased by 12,760.03 million rupiah. The purpose of this research is to determine the driving factors and inhibiting factors for the development of fisheries capture agribusiness. This was certainly supported by the direction of Spatial Plans of Penajam Paser Utara Regency in 2011-2031, namely realizing the Regency as the center of agribusiness. The methods used in this research were content analysis to identify driving and inhibiting factors of fisheriescatching agribusiness. The results obtained were as many as 21 variables were the driving factors for agribusiness development and 1 additional variable as an inhibiting factor namely the quality of the Fish Auction Place or TPI. Keywords: Regional Development, Fisheries Capture Agribusiness, Subsystem.